Subaltern Studies and Ecocriticism in La famosa invasione degli orsi in Sicilia by Dino Buzzati and Lorenzo Mattotti - Coglitore, Roberta (Quaderni d'Italianistica, 2022)
Lorenzo Mattotti’s 2019 adaptation of Dino Buzzati’s La famosa invasione degli orsi in Sicilia (1945) deserves special attention for three important reasons. First, Mattotti gives this long-undervalued work the preeminence it deserves as an iconotext that can be read by children and adults alike. Second, the movie introduces narrative elements from other works by Buzzati, ranging from Il deserto dei Tartari (1940) to I Miracoli di Val Morel (1971). Third, Mattotti’s film enhances two themes that were already present in Buzzati’s work: the contrast between human and animal perspectives, and the comparison between the city and the mountains. The filmic transposition develops these two themes: the first is transformed into a conflict between social groups, personifying issues that are highly debated today (the subaltern state, migration, postcolonialism); the second can be interpreted as an ecocritical rereading of Buzzati’s text. The struggle against social discrimination and the protection of the natural environment make Mattotti’s movie highly relevant because it addresses urgent contemporary issues.